Ternary positive electrode material, preparation method thereof and electrochemical device
Patent Information
- Application Number
- CN202511630924.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-07
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-11-07
AI Technical Summary
[0003]然而,三元正极材料存在储存性能较差、容量快速下降、安全性降低和使用寿命缩短等问题,阻碍了三元正极材料在动力电池和储能电池中的应用
1.三元正极材料复合包覆层中Li2TiO3和钾掺杂锂钨青铜二者协同作用,在提高三元正极材料的锂离子传输速率和电子导电率的同时,减少基体材料表面元素与电解液之间的副反应,延缓基体材料表面的金属溶出,并提高三元正极材料的结构稳定性,降低了三元正极材料颗粒的破碎风险,进而改善了三元正极料的存储性能。
Smart Images

Figure CN121439755B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, specifically to a ternary cathode material and its preparation method, and an electrochemical device. Background Technology
[0002] In recent years, automotive power batteries and stationary energy storage batteries have been at a critical stage of replacing traditional automobiles and the development of the energy industry. Lithium batteries are undergoing a crucial leap from scale expansion to high-quality development. Among them, cathode materials are the core of power and energy storage batteries, accounting for more than 40% of the battery cost. Ternary cathode materials, due to their high specific capacity, cycle life, and energy density, are widely used in new energy pure electric passenger vehicles and energy storage batteries.
[0003] However, ternary cathode materials suffer from problems such as poor storage performance, rapid capacity decline, reduced safety, and shortened lifespan, which hinder their application in power batteries and energy storage batteries. Summary of the Invention
[0004] In view of this, in order to solve at least one of the above technical problems, this application provides a ternary cathode material.
[0005] In addition, this application also provides a method for preparing a ternary cathode material and an electrochemical device.
[0006] In a first aspect, embodiments of this application provide a ternary cathode material, comprising: a matrix material and a composite coating layer located on the outer layer of the matrix material, wherein the matrix material comprises a ternary active material, and the composite coating layer contains Li2TiO3 and potassium-doped lithium tungsten bronze, wherein the potassium-doped lithium tungsten bronze is a non-stoichiometric compound, and the particle breakage index IC of the ternary cathode material satisfies 0≤IC≤0.40; wherein the method for obtaining the particle breakage index IC includes: assembling a cathode sheet containing the ternary cathode material into a battery; performing a first charge-discharge cycle on the battery, and continuing to charge to 100% SOC for load adjustment; and after load adjustment, randomly selecting m measurement sites on the surface of the cathode sheet of the battery, performing a crushing curve test on each measurement site to obtain m electrode pressure-displacement curves, and recording the number of curves with plateau characteristics in the m pressure-displacement curves as n, wherein m≥30, n≥0, and the particle breakage index IC=n / m.
[0007] Based on the first aspect, in some possible embodiments, the particle breakage index IC of the ternary cathode material satisfies 0≤IC≤0.25.
[0008] Based on the first aspect, in some possible embodiments, the composite coating layer accounts for 0.2wt% to 0.4wt% of the mass percentage of the ternary cathode material.
[0009] Based on the first aspect, in some possible embodiments, the matrix material is doped with W and / or Ti elements.
[0010] Secondly, this application provides a method for preparing a ternary cathode material, comprising: mixing and grinding a ternary precursor, a lithium source, a Ti source, and a W source to obtain a powder material, wherein the W source includes potassium-doped WO3; and loading the powder material into a packing device at a bulk density a, 0.7 g / cm³. 3 ≤a≤0.9g / cm 3 The powder material placed in the filling device is sintered in a low-oxygen atmosphere with an oxygen concentration of 20% to 40%, causing the ternary precursor and the lithium source to react to form a matrix material. The Ti source, the W source, and a portion of the lithium source react to form a composite coating layer on the surface of the matrix material. This composite coating layer contains Li₂TiO₃ and potassium-doped lithium tungsten bronze, wherein the potassium-doped lithium tungsten bronze is a non-stoichiometric compound. This yields the ternary cathode material.
[0011] Based on the second aspect, in some possible embodiments, the sintering includes a first stage sintering and a second stage sintering performed sequentially, wherein the temperature of the first stage sintering is lower than the temperature of the second stage sintering.
[0012] Based on the second aspect, in some possible embodiments, the sintering temperature of the first stage is 500℃~700℃, and the sintering time of the first stage is 5h~8h; and / or the sintering temperature of the second stage is 900℃~950℃, and the sintering time of the second stage is 8h~13h.
[0013] Based on the second aspect, in some possible embodiments, the preparation method satisfies at least one of the following conditions: (1) the amount of powder material loaded in the filling device is 3 / 4 to 4 / 5; (2) the molar ratio of Ti element in the Ti source to W element in the W source is (1 to 3): (3 to 1); (3) the total mass of the Ti source and the W source to the mass percentage of the ternary precursor is 0.2 wt% to 0.4 wt%.
[0014] Based on the second aspect, in some possible embodiments, the particle breakage index IC of the ternary cathode material satisfies 0 ≤ IC ≤ 0.40; wherein, the method for obtaining the particle breakage index IC includes: assembling a cathode sheet containing the ternary cathode material into a battery; performing a first charge-discharge cycle on the battery, and continuing to charge to 100% SOC for load adjustment; and after load adjustment, randomly selecting m measurement points on the surface of the cathode sheet of the battery, performing a crushing curve test on each measurement point to obtain m electrode pressure-displacement curves, and recording the number of curves with plateau characteristics in the m pressure-displacement curves as n, where m ≥ 30, n ≥ 0, then the particle breakage index IC = n / m.
[0015] Thirdly, embodiments of this application also provide an electrochemical device, the electrochemical device including a positive electrode sheet, the positive electrode sheet including a positive electrode material, the positive electrode material being the aforementioned ternary positive electrode material or a ternary positive electrode material prepared by the aforementioned preparation method.
[0016] Compared to existing technologies, the ternary cathode material provided in this application forms a composite coating layer on the surface of the ternary cathode material particles by mixing and coating the matrix material with Li2TiO3 and potassium-doped lithium tungsten bronze. In this composite coating layer, the synergistic effect of Li2TiO3 and potassium-doped lithium tungsten bronze stabilizes the structure of the matrix material and mitigates side reactions between the matrix material and the electrolyte, delaying the dissolution of transition metals such as nickel, cobalt, and manganese from the surface of the matrix material. This improves the interfacial stability of the ternary cathode material, thereby enhancing its cycle performance, storage performance, and safety performance. Furthermore, in the potassium-doped lithium tungsten bronze in the composite coating layer, the potassium doping helps to control the reduction of some hexavalent W to lower valence states, such as pentavalent and tetravalent W. These lower valence W states can provide free electrons, improving the electronic conductivity of the composite coating layer. Lithium ions can also migrate directionally within the channels of the potassium-doped lithium tungsten bronze crystal framework, further enhancing the electronic and lithium-ion conductivity of the ternary cathode material and reducing its internal resistance. In addition, the composite coating layer exhibits good stability, ensuring that the ternary cathode material meets the 0 ≤ IC ≤ 0.40 standard deviation. This effectively alleviates and disperses the external stress generated by the mutual compression between ternary cathode material particles during charging and discharging, reducing the risk of particle breakage during use and resulting in excellent cycle and storage performance of the prepared battery. Attached Figure Description
[0017] Figure 1 This is a schematic diagram illustrating the principle of the crush index (IC) test for ternary cathode materials. Figure 1 Figure (a) is a schematic diagram of the operation of the crush index (IC) test for ternary cathode material particles. Figure 1Figure (b) is a schematic diagram of the electrode pressure-displacement curve of the ternary cathode material particle crush index (IC) test.
[0018] Figure 2 This is a process flow diagram of the preparation method of the ternary cathode material provided in an embodiment of this application.
[0019] Figure 3 These are the pressure-displacement curves of 30 electrodes in Example 6 of this application for the ternary cathode material. Figure 3 Figure (a) shows the pressure-displacement curves for electrodes 1 through 10. Figure 3 Figure (b) shows the pressure-displacement curves for electrodes 11 through 20. Figure 3 Figure (c) shows the pressure-displacement curves of electrodes 21 to 30.
[0020] Figure 4 This application presents 30 electrode pressure-displacement curves of the ternary cathode material in Comparative Example 1. Figure 4 Figure (a) shows the pressure-displacement curves for electrodes 1 through 10. Figure 4 Figure (b) shows the pressure-displacement curves for electrodes 11 through 20. Figure 4 Figure (c) shows the pressure-displacement curves of electrodes 21 to 30.
[0021] Figure 5 High-temperature storage capacity retention curves of batteries prepared from ternary cathode materials in Examples 1-8 and Comparative Examples 1-2 of this application. Detailed Implementation
[0022] The embodiments of this application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain this application, and should not be construed as limiting this application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs; where there is no conflict, the implementation methods and features of the implementation methods of this application can be combined with each other; many specific details are set forth in the following description to provide a full understanding of this application, and the described implementation methods are only a part of the implementation methods of this application, and not all of the implementation methods.
[0023] Common methods for improving the interfacial stability of ternary cathode materials, thereby enhancing cycle and storage stability, include: modifying the ternary cathode material by doping it with appropriate amounts of other elements, such as Al, Fe, Mg, F, B, Mo, Zr, and W; or modifying the surface of the ternary cathode material by coating it with carbon, metal oxides, or metal composite salts. Through careful research and comparison, the inventors of this invention discovered that the anisotropic expansion / contraction of the lattice caused by lithium-ion insertion / extraction under high voltage can also lead to abrupt volume changes and particle breakage in ternary cathode materials. The cracking, deformation, and breakage of the aforementioned ternary cathode material particles are mainly affected by two factors: first, the degree of accumulation and uneven distribution of internal stress during use; and second, the degree and orientation distribution of external stress caused by mutual aggregation and compression between adjacent ternary cathode material particles on the battery cathode sheet. These problems of shortened lifespan, reduced capacity, and decreased safety of ternary cathode materials due to the coupling behavior of inhomogeneous electrochemistry and particle mechanics seriously hinder the further improvement of battery energy density through high-voltage processing of ternary cathode materials.
[0024] In view of this, this application proposes a novel ternary cathode material by studying the relationship between factors such as the composition and structure of the material body (matrix material) and the surface coating layer and the accumulation, distribution and orientation of internal and external stresses. This effectively solves the mechanical damage problem such as particle cracks that occur in ternary cathode materials during long-term use and storage, thereby improving the storage performance and cycle performance of the battery.
[0025] The novel ternary cathode material provided in this application includes: a matrix material and a composite coating layer located on the outer layer of the matrix material. The matrix material includes a ternary active material, and the composite coating layer contains Li2TiO3 and potassium-doped lithium tungsten bronze. The potassium-doped lithium tungsten bronze is a non-stoichiometric compound, and the particle breakage index IC of the ternary cathode material satisfies 0≤IC≤0.40. The method for obtaining the particle breakage index IC includes: assembling a positive electrode sheet containing ternary positive electrode material into a battery; performing the first charge and discharge cycle of the battery, and continuing to charge to 100% SOC for load adjustment; and after load adjustment, randomly selecting m measurement points on the surface of the positive electrode sheet of the battery, performing crushing curve tests on the m measurement points to obtain m electrode sheet pressure-displacement curves, and recording the number of curves with plateau characteristics among the m pressure-displacement curves as n, where m≥30 and n≥0, then the particle breakage index IC=n / m.
[0026] This application describes the formation of a protective composite coating layer on the surface of a substrate material containing Li2TiO3 and potassium-doped lithium tungsten bronze.
[0027] The potassium-doped lithium tungsten bronze in the composite coating layer exhibits excellent chemical stability and mechanical strength. It can isolate the matrix material from the electrolyte and apply mechanical constraints from the outside of the matrix material, suppressing the volume expansion and contraction of the ternary cathode material particles during cycling. This reduces the generation and propagation of microcracks in the ternary cathode material particles, maintaining their structural integrity. More importantly, potassium-doped lithium tungsten bronze is a non-stoichiometric compound (not an integral-stoichiometric chemical), and the W element in potassium-doped lithium tungsten bronze can include W... 4+ W 5+ and W 6+ This provides free electrons, improves the electronic conductivity of the composite coating layer, and creates an efficient electron transport network on the surface of the ternary cathode material, effectively reducing charge transfer impedance. Furthermore, potassium-doped lithium tungsten bronze possesses a tunnel structure, allowing lithium ions to migrate directionally within the channels of the potassium-doped lithium tungsten bronze crystal framework, thereby improving the lithium-ion insertion / extraction capability and ionic conductivity of the ternary cathode material. Therefore, the composite coating layer containing potassium-doped lithium tungsten bronze can form a hybrid conductor interface, simultaneously conducting electrons and ions, effectively compensating for the negative impact of the relatively low electronic conductivity of Li₂TiO₃ in the composite coating layer.
[0028] The Li₂TiO₃ in the composite coating layer exhibits high structural and thermal stability, as well as relatively high chemical inertness. Li₂TiO₃ can act as both a physical and chemical barrier, isolating the matrix material from the electrolyte, effectively reducing electrolyte erosion and the dissolution of transition metal ions from the matrix material, and constraining volume changes in the ternary cathode material, thereby improving the structural stability and integrity of the ternary cathode material particles.
[0029] The composite coating layer contains Li2TiO3 and potassium-doped lithium tungsten bronze, which work synergistically to improve the lithium-ion transport rate and electronic conductivity of the ternary cathode material, while reducing side reactions between the elements on the substrate material surface and the electrolyte, delaying the dissolution of metals on the substrate material surface, improving the structural stability of the ternary cathode material, reducing the risk of breakage of ternary cathode material particles, and thus improving the storage performance of the ternary cathode material.
[0030] In some embodiments, the composite coating layer can account for 0.2wt% to 0.4wt% of the ternary cathode material by mass, which is beneficial for balancing the protective effect of the composite coating layer on the matrix material and the high capacity of the ternary cathode material. This mass percentage can, exemplarily, be 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, or any value within the range of any two of the above values. The mass percentage can further be 0.3wt% to 0.35wt%.
[0031] In some embodiments, the matrix material may be doped with at least one element, W and Ti, which diffuse from the composite coating layer into the crystal structure of the matrix material, thereby further reducing the dissolution of transition metals and the loss of lattice oxygen in the matrix material.
[0032] In some embodiments, the matrix material can be a single crystal, which helps to reduce interfacial side reactions between the matrix material and the electrolyte, and improves the mechanical strength and structural stability of the ternary cathode material.
[0033] Furthermore, this application also controls the particle breakage index IC of the ternary cathode material to satisfy 0 ≤ IC ≤ 0.40. The particle breakage index IC reflects the degree of breakage of the ternary cathode material particles caused by the application of external stress under electrochemical stress conditions. When IC satisfies 0 ≤ IC ≤ 0.40, it indicates that the composite coating layer has good stability and strong interfacial bonding between the composite coating layer and the matrix material. This effectively alleviates and disperses the external stress generated by the mutual compression between particles on the cathode sheet during the charging and discharging process of lithium batteries using this ternary cathode material, effectively reducing the risk of ternary cathode material particle breakage during lithium battery use, and enabling the lithium battery to have excellent high-temperature cycle performance and storage performance. For example, the particle breakage index IC of the ternary cathode material can be 0, 0.01, 0.02, 0.03, 0.05, 0.06, 0.08, 0.1, 0.12, 0.15, 0.18, 0.2, 0.22, 0.25, 0.28, 0.29, 0.3, 0.33, 0.35, 0.38, 0.4 or any value within the range of any two of the above values.
[0034] Furthermore, the particle breakage index IC of the ternary cathode material can meet the requirement of 0≤IC≤0.25. The IC value of the ternary cathode material is less than or equal to 0.25, which further improves the stability of the composite coating layer and the overall mechanical strength of the ternary cathode material. The ternary cathode material particles are not easy to break, and the storage performance is further improved.
[0035] The particle crushing index (IC) is obtained by performing a crushing curve test on a ternary cathode material cathode sheet at 100% SOC, and then measuring and counting the pressure-displacement curves of the cathode sheet that passed the crushing curve test. Specifically, the internal chemical reaction of the battery is first activated through the first charge-discharge cycle to form a stable electrochemical structure, and the battery is then charged to 100% SOC for load adjustment. Then, the battery at 100% SOC is disassembled to obtain the cathode sheet, and a crushing curve test is performed on the cathode sheet. The crushing curve test is performed on a single particle crushing device. The cathode sheet is fixed to the surface of the carrier with a fixative liquid and then placed on the sample stage directly below the pressure probe. The pressure-displacement curves of the cathode sheet at m random measurement points are obtained. The horizontal axis of the electrode pressure-displacement curve represents displacement, and the vertical axis represents the external pressure applied at the measurement point. Pressure-displacement curves at different measurement sites may exhibit different trends. When the pressure change shows a clear inflection point as the displacement changes on the curve, it is generally characterized by a significant decrease in the slope of the pressure-displacement curve, known as a plateau feature. This plateau feature indicates that the ternary cathode material particles in contact with the indenter have broken up in the test site region of the positive electrode. Figure 1 As shown, since the cathode sheet containing ternary cathode material contains multiple particles in the vertical direction, it is possible for no particles to be crushed (Case 1), one particle to be crushed (Case 2), or multiple particles to be crushed sequentially (Case 3). The corresponding electrode pressure-displacement curves are: no plateau feature (Case 1), one plateau feature (Case 2), and multiple plateau features (Case 3). When the electrode pressure-displacement curve has a plateau feature (i.e., the number of plateau features ≥ 1), the electrode pressure-displacement curve is recorded as unqualified. The number of unqualified electrode pressure-displacement curves among m electrode pressure-displacement curves is recorded as n, that is, the number of curves with plateau features among m pressure-displacement curves is recorded as n. The particle breakage index IC = n / m. Wherein, m ≥ 30 can more accurately reflect the particle breakage index of ternary cathode material. m can be exemplarily 30, 40, 50, 60, 70, 80, 90, or 100, etc. The range of m can be 30 ≤ m ≤ 100. Understandably, increasing the number of measurement sites m helps reduce statistical error and makes the test results closer to the true value. m includes, but is not limited to, the values mentioned above.
[0036] In the step of assembling a positive electrode plate containing a ternary cathode material into a battery, the preparation method of the positive electrode plate containing the ternary cathode material is not particularly limited. For example, a positive electrode slurry containing the ternary cathode material, a conductive agent, a binder and a solvent may be coated on a positive electrode current collector (such as aluminum foil or carbon-coated aluminum foil), and dried to form a positive electrode film layer, thereby obtaining the positive electrode plate. The assembled battery may be a half coin cell, and the negative electrode plate of the half coin cell may be a lithium sheet.
[0037] The step of subjecting the battery to first-cycle charge-discharge and continuing charging to 100% SOC for capacity regulation may exemplarily include: charging the battery at a constant current of 0.1C rate to 4.45V at 25°C, charging at a constant voltage of 4.45V to a cut-off rate of 0.02C, and discharging at a constant current of 0.1C rate to 2.8V to complete the first-cycle charge-discharge; and charging the battery after completion of the first-cycle charge-discharge at a constant current of 0.1C rate to a cut-off voltage of 4.45V, and then charging at a constant voltage of 4.45V to a cut-off rate of 0.02C, to obtain a battery regulated to 100% SOC.
[0038] In some embodiments, the battery regulated to 100% SOC is disassembled, and the disassembly time is t, where 0 < t ≤ 30 min. Rapid disassembly of the battery within 30 min is beneficial for the phase structure of the ternary cathode material in the positive electrode plate to remain in the capacity-regulated state, improving the detection accuracy.
[0039] In some embodiments, after obtaining the positive electrode plate from the battery regulated to 100% SOC, the positive electrode plate may also be washed with an organic solvent, dried in vacuum, and then fixed on the surface of a carrier with a fixing solution, before performing the crushing curve test.
[0040] Further, the organic solvent may be selected according to the electrolyte in the assembled battery, for example, may be selected from carbonate solvents and carboxylate solvents. Further, the organic solvent may include at least one of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), propylene carbonate (PC), and vinylene carbonate (VC).
[0041] In some embodiments, the temperature of vacuum drying may be 20°C to 40°C. Exemplarily, it may be 20°C, 25°C, 30°C, 35°C, 40°C, or any value within the range composed of any two of the above values. The temperature of vacuum drying may further be room temperature.
[0042] In some embodiments, the fixing solution may include at least one of water, ethanol, butanol, glycerol, and the like.
[0043] Compared with the prior art, the ternary cathode material of the present application has the following beneficial effects: 1. The synergistic effect of Li₂TiO₃ and potassium-doped lithium tungsten bronze in the composite coating layer of the ternary cathode material can increase the lithium ion transmission rate and electronic conductivity of the ternary cathode material, reduce side reactions between elements on the surface of the base material and the electrolyte, delay metal dissolution on the surface of the base material, improve the structural stability of the ternary cathode material, reduce the crushing risk of ternary cathode material particles, and thereby improve the storage performance of the ternary cathode material.
[0044] 2. The particle breakage index IC of the ternary cathode material satisfies 0≤IC≤0.40, which indicates that the composite coating layer also has high stability, can effectively relieve and disperse the external stress generated by mutual extrusion between particles on the positive electrode plate during charge and discharge of a lithium battery using the ternary cathode material, reduce the risk of particle breakage of the ternary cathode material, and endows the ternary cathode material with good storage performance.
[0045] Please refer to Figure 2 , based on the same inventive concept, embodiments of the present application also provide a preparation method of a ternary cathode material, specifically comprising the following steps: Step S1: mixing a ternary precursor, a lithium source, a Ti source and a W source, and grinding the mixture to obtain a powder material, wherein the W source comprises potassium-doped WO₃.
[0046] Specifically, mixing a ternary precursor, a lithium source, a Ti source and a W source in a certain proportion, and grinding the mixture to obtain a uniform powder material. Wherein, the chemical formula of the ternary precursor can be Ni y Co z Mn 1-y-z (OH)₂, 0<y<1, 0<z<1, and 0<y+z<1. The W source comprises potassium-doped WO₃. Grinding methods include, but are not limited to, ball milling. It can be understood that any method capable of refining materials and uniformly mixing the materials is applicable.
[0047] In some embodiments, the lithium source may comprise at least one of lithium hydroxide, lithium carbonate, etc.; the Ti source may comprise at least one of titanium dioxide, strontium titanate, etc.
[0048] Step S2: loading the powder material into a filling device at a bulk density a, 0.7g / cm 3 ≤a≤0.9g / cm 3 .
[0049] Specifically, loading the powder material into the filling device at the above-mentioned high bulk density a is conducive to forcing close contact between powder material particles and reducing contact between powder material particles and oxygen. Wherein, increasing the bulk density a of the powder material can be achieved by increasing the loading amount and reducing the bulk volume of the powder material.
[0050] For example, a can be 0.7 g / cm³. 3 0.72g / cm 3 0.75g / cm 3 0.8g / cm 3 0.85g / cm 3 0.9g / cm 3 Or any value within the range formed by any two of the above values. a can further be 0.8 g / cm³. 3 ≤a≤0.9g / cm 3 This is beneficial for further increasing the density of powder materials and further reducing the contact between powder material particles and oxygen.
[0051] In some embodiments, the amount of powder material loaded in the packing device can be 3 / 4 to 4 / 5, which is beneficial to balance the uniformity of the reaction and the yield in the subsequent sintering.
[0052] Step S3: The powder material placed in the filling device is sintered in a low oxygen atmosphere with an oxygen concentration of 20%~40%, so that the ternary precursor and the lithium source react to form a matrix material, and the Ti source, W source and part of the lithium source react to form a composite coating layer on the surface of the matrix material. The composite coating layer contains Li2TiO3 and potassium-doped lithium tungsten bronze, wherein the potassium-doped lithium tungsten bronze is a non-stoichiometric compound, thereby obtaining a ternary cathode material.
[0053] Specifically, under a low-oxygen atmosphere, powder materials placed in a filling device are sintered to obtain ternary cathode materials. During this sintering process, the ternary precursor and lithium source in the powder material react to generate a matrix material containing ternary active materials. Simultaneously, the Li source, W source, and Ti source react in situ on the outer layer of this matrix material to form Li₂TiO₃ and potassium-doped lithium tungsten bronze, thus forming a composite coating layer. The oxygen concentration in the low-oxygen atmosphere is 20%–40%, which helps to further reduce the contact between the powder material and oxygen while controlling the packing density 'a'. This further regulates the valence state of W in the potassium-doped lithium tungsten bronze, reducing W oxidation and maintaining its reducing properties during sintering. This ensures that at least some W remains in a low valence state (below +6), promoting lithium-ion diffusion and electron transitions, thereby improving the lithium-ion conductivity and electronic conductivity of the composite coating layer. Understandably, the composite coating layer may also contain unreacted residual lithium from the tungsten source (potassium-doped WO₃).
[0054] This composite coating layer possesses excellent mechanical properties, structural stability, chemical stability, lithium-ion conductivity, and electronic conductivity. It can stabilize the structure of the matrix material and mitigate side reactions between the matrix material and the electrolyte, as well as delay the dissolution of transition metals such as nickel, cobalt, and manganese from the surface of the matrix material. This improves the cycle performance, storage performance, safety, and rate performance of the ternary cathode material.
[0055] The oxygen concentration of the low-oxygen atmosphere is 20% to 40%, and can be, for example, 20%, 25%, 30%, 35%, 40%, or any value within the range of any two of the above values. The oxygen concentration of the low-oxygen atmosphere can further be 25% to 35%.
[0056] In some embodiments, the molar ratio of Li in the lithium source to Ni, Co and Mn in the ternary precursor, Li:(Ni+Co+Mn), can be 1.02~1.05. The slightly higher molar amount of Li is beneficial for the excess Li to react with the Ti source and W source to generate Li2TiO3 and potassium-doped lithium tungsten bronze.
[0057] In some embodiments, potassium-doped WO3 can be prepared by a hydrothermal reaction method. The preparation method mainly includes: dissolving tungstate in ultrapure water to prepare a solution; passing the solution through a cation exchange resin column for complete exchange to obtain tungstate colloid; adding a dopant element solution to the tungstate colloid, allowing it to cool naturally to room temperature and aging; subjecting the aged colloidal solution to a hydrothermal reaction at 160°C~180°C, followed by alcohol washing, water washing, and drying to obtain potassium-doped WO3, wherein the dopant element solution is a potassium salt solution. It is understood that the preparation method of potassium-doped WO3 includes, but is not limited to, the above method, as long as potassium-doped WO3 can be obtained.
[0058] Furthermore, the mass percentage of potassium in the potassium salt solution and W in the tungstate is preferably 0.057wt% to 0.1wt%, that is, the amount of potassium doping in potassium-doped WO3 can be 0.057wt% to 0.1wt%.
[0059] In some embodiments, the total mass percentage of the Ti source and W source to the ternary precursor can be 0.2wt% to 0.4wt%, which is beneficial for forming a composite coating layer of suitable thickness on the surface of the matrix material, and for balancing the protective effect of the composite coating layer on the matrix material and the high capacity of the ternary cathode material. This mass percentage can, exemplarily, be 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, or any value within the range of any two of the above values. The mass percentage can further be 0.3wt% to 0.35wt%.
[0060] In some embodiments, the molar ratio of Ti element in the Ti source to W element in the W source can be (1~3):(3~1), which is beneficial for adjusting the proportion of Li2TiO3 and potassium-doped lithium tungsten bronze in the composite coating layer, and for the composite coating layer to balance structural stability, lithium-ion conductivity and electronic conductivity. The molar ratio of Ti element in the Ti source to W element in the W source can, for example, be 3:1, 2.5:1, 2:1, 1.5:1, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, or any value within the range of any two of the above values. The molar ratio of Ti element in the Ti source to W element in the W source can further be (1~1.5):(1~2.5).
[0061] The sintering process can include a first-stage sintering and a second-stage sintering, performed sequentially, with the temperature of the first-stage sintering being lower than that of the second-stage sintering. The lower temperature of the first-stage sintering facilitates the removal of volatile components, reducing cracks, voids, or other defects caused by the escape of volatile components during the second-stage sintering, thus improving the uniformity of the sintering and consequently enhancing the quality of the matrix material. The higher temperature of the second-stage sintering promotes the in-situ reaction of Li with the Ti and W sources to form a composite coating layer, and strengthens the adhesion between this composite coating layer and the matrix material, making it less prone to detachment and improving the structural stability of the ternary cathode material. Furthermore, the higher temperature of the second-stage sintering also facilitates the incorporation of Ti and W elements into the bulk phase of the matrix material, resulting in metal element doping.
[0062] Specifically, the sintering temperature of the first stage can be 500℃~700℃, and for example, it can be 500℃, 530℃, 550℃, 600℃, 650℃, 700℃, or any value within the range of any two of the above values; the sintering time of the first stage is 5h~8h, and for example, it can be 5h, 6h, 7h, 8h, or any value within the range of any two of the above values. The sintering temperature of the second stage can be 900℃~950℃, and for example, it can be 900℃, 910℃, 920℃, 930℃, 940℃, 950℃, or any value within the range of any two of the above values. The sintering time of the second stage can be 8h~13h, and for example, it can be 8h, 9h, 10h, 11h, 12h, 13h, or any value within the range of any two of the above values.
[0063] In some embodiments, the particle breakage index IC of the ternary cathode material satisfies 0 ≤ IC ≤ 0.40; wherein, the method for obtaining the particle breakage index IC includes: assembling a cathode sheet containing ternary cathode material into a battery; performing a first charge-discharge cycle on the battery and continuing to charge to 100% SOC for load adjustment; and after load adjustment, randomly selecting m measurement points on the surface of the cathode sheet of the battery, performing a crushing curve test on each measurement point to obtain m electrode pressure-displacement curves, and recording the number of curves with plateau characteristics among the m pressure-displacement curves as n, where m ≥ 30, n ≥ 0, then the particle breakage index IC = n / m.
[0064] Compared with existing technologies, the preparation method of the ternary cathode material in this application has the following advantages: 1. Controlling the bulk density 'a' of the powder material to be sintered and the oxygen content of the sintering atmosphere is beneficial for close contact between powder particles and reduces contact between powder particles and oxygen. This helps to regulate the valence state of W in potassium-doped lithium tungsten bronze, reduce the oxidation of W, and help maintain the reducing properties of potassium-doped lithium tungsten bronze during sintering. This ensures that at least some W remains in a low valence state (below +6), promoting the diffusion of lithium ions and the transition of electrons, thereby improving the lithium-ion conductivity and electronic conductivity of the composite coating layer.
[0065] 2. Simultaneous in-situ reaction on the surface of the matrix material generates Li2TiO3 and potassium-doped lithium tungsten bronze to form a composite coating layer, which can improve the lithium-ion conductivity, electronic conductivity and structural stability of the ternary cathode material. While improving the rate performance of the ternary cathode material, it effectively alleviates and disperses the external stress generated by the mutual compression between the particles of the ternary cathode material, reduces the risk of particle breakage, and enables the lithium battery to have excellent cycle performance and storage performance.
[0066] This application also provides an electrochemical device (e.g., a secondary battery) comprising a positive electrode plate, the positive electrode plate comprising a positive electrode material, wherein the positive electrode material is the aforementioned ternary positive electrode material. Compared with the prior art, the electrochemical device provided in this application has good rate performance, cycle performance, and storage performance.
[0067] Typically, an electrochemical device may also include a negative electrode, a separator, and an electrolyte. During battery charging and discharging, active ions repeatedly insert and extract between the positive and negative electrodes. The electrolyte acts as a conductor of ions between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, prevents short circuits while allowing ions to pass through.
[0068] In some embodiments, the positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector, the positive electrode film layer comprising the ternary positive electrode material. The positive current collector can be aluminum foil or carbon-coated aluminum foil. The positive electrode film layer may also contain a binder, such as polyvinylidene fluoride (PVDF). The positive electrode film layer also contains a conductive agent, such as at least one selected from superconducting carbon, acetylene black, carbon black, carbon nanotubes, and graphene.
[0069] In some embodiments, the negative electrode may be a lithium sheet.
[0070] In some embodiments, the negative electrode sheet may include a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector. The negative current collector may be a metal current collector, such as copper foil. The negative electrode film layer may contain a negative electrode active material. Negative electrode active materials are well known in the art, and this application does not particularly limit them. The negative electrode active material may be selected from at least one of the following materials: graphite, soft carbon, hard carbon, silicon-based materials, and lithium titanate, etc.
[0071] In some embodiments, the negative electrode film layer may further include a binder. The binder used for the negative electrode is, for example, at least one selected from styrene-butadiene rubber, polyacrylic acid, polyacrylamide, and carboxymethyl cellulose. In some embodiments, the negative electrode film may also contain a conductive agent, such as one or more of the following materials: superconducting carbon, acetylene black, carbon black, graphene, carbon nanotubes, etc.
[0072] The electrolyte can be selected based on existing lithium battery specifications. Generally, the electrolyte contains an organic solvent and an electrolyte lithium salt. The electrolyte salt includes, but is not limited to: lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, and bis(fluorosulfonyl)imide. Organic solvents include, but are not limited to: ethyl methyl carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, methyl formate, methyl acetate, propyl acetate, methyl propionate, and ethyl propionate.
[0073] This application does not impose any particular restrictions on the type of diaphragm; various porous diaphragms well-known in the art can be selected. The material of the diaphragm can be, for example, polyethylene, polypropylene, or polyvinylidene fluoride.
[0074] The electrochemical device of the present invention may be in the form of a single battery cell, a battery module, or a battery pack.
[0075] The present application's solution will be explained below with reference to embodiments. Those skilled in the art will understand that the following examples are for illustrative purposes only and should not be construed as limiting the scope of the application. Unless otherwise stated, reagents, software, and instruments involved in the following embodiments that are not specifically described are all conventional commercially available products or publicly disclosed.
[0076] Example 1 Step S1: [The following appears to be a separate, unrelated sentence:] Ni 0.6 Co 0.2 Mn 0.2 The ternary precursor (OH)2, LiOH, TiO2, and potassium-doped WO3 were mixed and ground using a ball mill to obtain a powder material. The molar ratio of Li in LiOH to Ni, Co, and Mn in the ternary precursor, Li:(Ni+Co+Mn), was 1.05. The mass percentage of TiO2 and potassium-doped WO3 to the ternary precursor was 0.2wt%, the molar ratio of Ti to W was 3:1, and the potassium doping amount in potassium-doped WO3 was 0.057wt%~0.1wt%.
[0077] Step S2: The powder material is loaded into the sagger of the packing device at a bulk density of α, where α is 0.7 g / cm³. 3 The sagger dimensions are 330mm×330mm×65mm, and the amount of powder material in the sagger is 4 / 5.
[0078] Step S3: Under a low-oxygen atmosphere with an oxygen concentration of 20%, the powder material placed in a sagger is sintered, cooled, and then pulverized by airflow. During the sintering process, the ternary precursor and LiOH react to generate a matrix material containing ternary active substances, and some LiOH reacts with TiO2 and potassium-doped WO3 to form a composite coating layer on the surface of the matrix material. The composite coating layer contains Li2TiO3 and potassium-doped lithium tungsten bronze, thereby obtaining a single-crystal ternary cathode material. The sintering process includes a first stage sintering at 650°C for 7 hours, followed by a second stage sintering at 900°C for 10 hours.
[0079] Example 2: The difference from Example 1 is that the bulk density α in step S2 is 0.75 g / cm³. 3 The preparation methods for the remaining ternary cathode materials are basically the same as those in Example 1.
[0080] Example 3: The difference from Example 1 is that in step S2, the bulk density a is 0.9 g / cm³. 3 The preparation methods for the remaining ternary cathode materials are basically the same as those in Example 1.
[0081] Example 4: The difference from Example 1 is that in step S1, the molar ratio of Ti to W is 1:1. The preparation methods of the remaining ternary cathode materials are basically the same as in Example 1.
[0082] Example 5: The difference from Example 1 is that in step S1, the molar ratio of Ti to W is 1:3. The preparation methods of the remaining ternary cathode materials are basically the same as in Example 1.
[0083] Example 6: The difference from Example 1 is that in step S1, the mass percentage of TiO2 and potassium-doped WO3 to the ternary precursor is 0.3 wt%. The preparation method of the remaining ternary cathode materials is basically the same as that in Example 1.
[0084] Example 7: The difference from Example 1 is that in step S1, the mass percentage of TiO2 and potassium-doped WO3 to the ternary precursor is 0.4 wt%. The preparation method of the remaining ternary cathode materials is basically the same as that in Example 1.
[0085] Example 8: The difference from Example 1 is that in step S3, the oxygen concentration of the low-oxygen atmosphere is 40%. The preparation methods of the remaining ternary cathode materials are basically the same as those in Example 1.
[0086] Comparative Example 1: Step S1: [The following appears to be a separate, unrelated sentence:] Ni 0.6 Co 0.2 Mn 0.2 The ternary precursor of (OH)2, LiOH and TiO2 were mixed and ground in a ball mill to obtain a powder material. The molar ratio of Li in LiOH to Ni, Co and Mn in the ternary precursor, Li:(Ni+Co+Mn) was 1.05, and the mass percentage of TiO2 to the ternary precursor was 0.2wt%.
[0087] Step S2: The powder material is loaded into the sagger of the packing device at a bulk density of α, where α is 0.7 g / cm³. 3 The sagger dimensions are 330mm×330mm×65mm, and the amount of powder material in the sagger is 4 / 5.
[0088] Step S3: Under a low-oxygen atmosphere with an oxygen concentration of 20%, the powder material placed in a sagger is sintered, cooled, and then pulverized by airflow. During the sintering process, the ternary precursor in the powder material reacts with LiOH to generate a matrix material containing ternary active substances, and the Li and Ti elements form a Li2TiO3 coating layer on the surface of the matrix material, thereby obtaining a single-crystal ternary cathode material. The sintering process includes a first stage sintering at 650℃ for 7 hours, followed by a second stage sintering at 900℃ for 10 hours.
[0089] Comparative Example 2 Step S1: [The following appears to be a separate, unrelated sentence:] Ni 0.6 Co 0.2 Mn 0.2The ternary precursor (OH)2, LiOH, and potassium-doped WO3 were mixed and ground using a ball mill to obtain a powder material. The molar ratio of Li in LiOH to Ni, Co, and Mn in the ternary precursor, Li:(Ni+Co+Mn), was 1.05. The mass percentage of WO3 to the ternary precursor was 0.2wt%, and the potassium doping amount in the potassium-doped WO3 was 0.057wt%~0.1wt%.
[0090] Step S2: The powder material is loaded into the sagger of the packing device at a bulk density of α, where α is 0.7 g / cm³. 3 The sagger dimensions are 330mm×330mm×65mm, and the amount of powder material in the sagger is 4 / 5.
[0091] Step S3: Under a low-oxygen atmosphere with an oxygen concentration of 20%, the powder material placed in a sagger is sintered, cooled, and then pulverized by airflow. During the sintering process, the ternary precursor in the powder material reacts with LiOH to generate a matrix material containing ternary active substances, and LiOH and potassium-doped WO3 form a potassium-doped tungsten bronze coating layer on the surface of the matrix material, thereby obtaining a single-crystal ternary cathode material. The sintering process includes a first stage sintering at 650℃ for 7 hours, followed by a second stage sintering at 900℃ for 10 hours.
[0092] Comparative Example 3 Step S1: [The following appears to be a separate, unrelated sentence:] Ni 0.6 Co 0.2 Mn 0.2 The ternary precursor of (OH)2, LiOH, TiO2 and WO3 were mixed and ground in a ball mill to obtain a powder material. The molar ratio of Li in LiOH to Ni, Co and Mn in the ternary precursor, Li:(Ni+Co+Mn) was 1.05. The mass percentage of TiO2 and WO3 to the ternary precursor was 0.2wt%. The molar ratio of Ti to W was 3:1.
[0093] Step S2: The powder material is loaded into the sagger of the packing device at a bulk density of α, where α is 0.6 g / cm³. 3 The sagger dimensions are 330mm×330mm×65mm, and the amount of powder material in the sagger is 4 / 5.
[0094] Step S3: Under an atmosphere with an oxygen concentration of 20%, the powder material placed in a sagger is sintered, cooled, and then pulverized by airflow. During the sintering process, the ternary precursor in the powder material reacts with LiOH to generate a matrix material containing ternary active substances, and the Li element, W element, and Ti element form a composite coating layer containing WO3, Li2TiO3, and Li2WO4 on the outer layer of the matrix material, thereby obtaining a single-crystal ternary cathode material. The sintering process includes a first stage sintering at 650℃ for 7 hours, followed by a second stage sintering at 900℃ for 10 hours.
[0095] The ternary cathode materials obtained in Examples 1-8 and Comparative Examples 1-3 were subjected to the following tests.
[0096] 1. Particle breakage index (IC) test: Preparation of button half-cells: Lithium-ion battery positive electrode material, conductive agent Super P, and binder PVDF were weighed at a mass ratio of 94:2:4 and mixed with solvent NMP. The slurry viscosity was controlled to 8000 mPa·s in a degassing machine. Then, the slurry was uniformly coated onto carbon-coated aluminum foil using an automatic coating machine to form the original electrode sheet. The electrode sheet was dried in a vacuum oven at 130°C for 4 hours, and then placed in a forced-air oven at 80°C for 12 hours to obtain the test sheet. Several small electrode sheets were cut from different positions of the test sheet using a 14 mm diameter die. Small electrode sheets with regular morphology and smooth surfaces and edges were selected and weighed using a 0.01 g balance to determine the positive electrode material of the electrode sheet. To obtain the positive electrode, the weighed small electrode sheet was placed in a vacuum drying oven, evacuated to 0.1 MPa, and dried for 12 hours. The positive electrode sheet was then stored for later use. In an inert gas glove box with water and oxygen content of less than or equal to 0.0005%, a coin cell was assembled according to the battery specifications of CR2023. The negative electrode was a lithium sheet, the separator was a polypropylene membrane, and the electrolyte was a 1M lithium hexafluorophosphate solution (the solvent was a mixture of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1). After assembly, the cells were sealed at 800 Pa for 5 seconds to obtain a coin cell half-cell.
[0097] Electrode pressure-displacement test: (1) The button half-cell was charged and discharged for the first time at 25°C. The specific process was as follows: at 25°C, it was charged at a constant current of 0.1C to 4.45V (vs Li), charged at a constant voltage of 4.45V (vs Li) to the cutoff rate of 0.02C, and discharged at a constant current of 0.1C to 2.8V (vs Li).
[0098] (2) Charge the test sample at a constant current at a rate of 0.1C to the cutoff voltage of 4.45V (vs Li), and then charge it at a constant voltage at a potential of 4.45V (vs Li) to the cutoff rate of 0.02C.
[0099] (3) For the button cell that has been charged to full charge, i.e. 100% SOC, disassemble and remove the positive electrode to be tested within 30 minutes, clean it with EMC for 10 minutes, vacuum dry it at room temperature for 30 minutes, and then perform the electrode pressure-displacement curve test.
[0100] (4) The pressure-displacement curve test of the electrode was carried out on a single particle crushing device. The electrode to be tested was fixed on a special glass slide with pure water and then placed on the sample stage directly below the pressure probe. The pressure-displacement curves of m random sampling points on each sample electrode were obtained, resulting in m electrode pressure-displacement curves. In this test, m was set to 30.
[0101] (5) The number of curves with plateau characteristics in the m pressure-displacement curves obtained for each electrode is denoted as n, and the particle breakage index IC = n / m.
[0102] 2. High-temperature storage performance test: Fabrication of the pouch cell: The pouch cell was fabricated using conventional processes. The designed capacity is 2 Ah. It employs a Z-shaped stacking design with 7 layers of double-sided positive electrodes and 8 layers of double-sided negative electrodes. The N / P ratio is 1.13. The effective dimensions of the positive electrode are 59 × 79 mm, and the effective dimensions of the negative electrode are 61 × 81 mm. The positive electrode composition is ternary cathode material: conductive carbon: CNT: PVDF = 96%: 0.8%: 1.2%: 2%, with a compaction density controlled at 3.5 g / cm³. 3 The negative electrode composition is approximately 95.1% G49 : conductive carbon : CMC : SBR : 2.5%, with a compaction density controlled at 1.6 g / cm³. 3 about.
[0103] According to the above design, the corresponding positive and negative electrodes are manufactured using conventional processes such as slurry preparation, coating, drying, and rolling. These electrodes are then cut into appropriately sized sheets, stacked, and have their tabs welded, and packaged to create a soft-pack dry cell with one open side. The cells are then transferred to a glove box, 7 ml of electrolyte is injected, and the box is sealed. The cells are left to stand at 45°C for at least 8 hours to allow the electrolyte to fully wet the positive and negative electrodes. Subsequently, formation and capacity testing are performed.
[0104] High-temperature storage performance test: The pouch cells, after being sized and tested, underwent a pre-high-temperature storage charge-discharge test. They were placed in an environment at 25°C and the charge-discharge test was performed according to the procedures and parameters in Table 1 below. Before storage, the cell capacity was tested to obtain the battery's discharge capacity at room temperature (capacity in step 5 of Table 1), defined as the pre-high-temperature capacity. The batteries were then charged to 4.40V. The pouch cells were then transferred to an 80°C high-temperature storage test chamber. Every 7 days, one pouch cell was taken from the sample and placed in an environment at 25°C for at least 4 hours. Subsequently, a post-storage charge-discharge test was performed according to the procedures and parameters in Table 2 below to obtain the battery's discharge capacity after high-temperature storage (capacity in step 2 of Table 2). The capacity retention rate in the high-temperature storage performance test = post-high-temperature capacity / pre-high-temperature capacity × 100%.
[0105] Table 1 Table 2 The test results of Examples 1-8 and Comparative Examples 1-3 are shown in Table 3 and Figures 3 to 5 As shown.
[0106] Table 3 The above results indicate that: Combined with Table 3, and Figures 3 to 5 It can be seen that, compared with Comparative Examples 1-3, the particle breakage index (IC) of the ternary cathode materials provided in Examples 1-8 is less than or equal to 0.4, that is, with a total sampling point of 30, the number of curves containing one or more plateaus is less than or equal to 12. Using the ternary cathode materials provided in Examples 1-8 as cathode materials to prepare batteries can effectively alleviate and disperse the external stress generated by the mutual compression between particles on the electrode during the charging and discharging process of lithium batteries, reducing the risk of particle breakage during use. This results in lithium batteries with excellent high-temperature storage performance. The lithium batteries prepared with the ternary cathode materials in Examples 1-8, after being placed at high temperatures for 56 days, showed higher volume retention rates every 7 days compared to Comparative Examples 1-3. This is because the composite coating layer in Examples 1-8 has good stability, containing Li2TiO3 and potassium-doped lithium tungsten bronze, whose synergistic effect improves the structural stability and storage performance of the ternary cathode material.
[0107] It is understood that the above embodiments are merely exemplary implementations used to illustrate the principles of the present invention, and the present invention is not limited thereto. For those skilled in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. A ternary cathode material, characterized in that, include: The matrix material and the composite coating layer located on the outer layer of the matrix material, wherein the matrix material includes a ternary active material, and the composite coating layer contains Li2TiO3 and potassium-doped lithium tungsten bronze, wherein the potassium-doped lithium tungsten bronze is a non-stoichiometric compound, and the particle breakage index IC of the ternary cathode material satisfies 0≤IC≤0.40; The method for obtaining the particle breakage index IC includes: The cathode sheet containing the ternary cathode material is assembled into a battery; The battery undergoes its first charge-discharge cycle, and is then charged to 100% SOC for load adjustment; and After load adjustment, m measurement points are randomly selected on the surface of the positive electrode of the battery. Crushing curve test is performed on each measurement point to obtain m electrode pressure-displacement curves. The number of curves with plateau characteristics in the m pressure-displacement curves is recorded as n, where m≥30 and n≥0. Then the particle breakage index IC=n / m.
2. The ternary cathode material as described in claim 1, characterized in that, The particle breakage index IC of the ternary cathode material satisfies 0 ≤ IC ≤ 0.
25.
3. The ternary cathode material as described in claim 1, characterized in that, The composite coating layer accounts for 0.2wt% to 0.4wt% of the ternary cathode material by mass.
4. The ternary cathode material as described in claim 1, characterized in that, The matrix material is doped with W and / or Ti elements.
5. A method for preparing a ternary cathode material, characterized in that, include: A ternary precursor, a lithium source, a Ti source, and a W source are mixed and ground to obtain a powder material, wherein the W source includes potassium-doped WO3. The powder material is loaded into the packing device at a bulk density of 0.7 g / cm³. 3 ≤a≤0.9g / cm 3 ;as well as The powder material placed in the filling device is sintered in a low-oxygen atmosphere with an oxygen concentration of 20% to 40%, so that the ternary precursor and the lithium source react to form a matrix material, and the Ti source, the W source and part of the lithium source react to form a composite coating layer covering the surface of the matrix material. The composite coating layer contains Li2TiO3 and potassium-doped lithium tungsten bronze, wherein the potassium-doped lithium tungsten bronze is a non-stoichiometric compound, thereby obtaining the ternary cathode material.
6. The preparation method according to claim 5, characterized in that, The sintering includes a first stage sintering and a second stage sintering performed sequentially, wherein the temperature of the first stage sintering is lower than the temperature of the second stage sintering.
7. The preparation method according to claim 6, characterized in that, The sintering temperature of the first stage is 500℃~700℃, and the sintering time of the first stage is 5h~8h; and / or The sintering temperature of the second stage is 900℃~950℃, and the sintering time of the second stage is 8h~13h.
8. The preparation method according to claim 5, characterized in that, The preparation method satisfies at least one of the following conditions: (1) The amount of powder material loaded in the filling device is 3 / 4 to 4 / 5; (2) The molar ratio of Ti element in the Ti source to W element in the W source is (1~3):(3~1); (3) The total mass of the Ti source and the W source is 0.2wt% to 0.4wt% of the mass of the ternary precursor.
9. The preparation method according to claim 5, characterized in that, The particle breakage index IC of the ternary cathode material satisfies 0 ≤ IC ≤ 0.40; The method for obtaining the particle breakage index IC includes: The cathode sheet containing the ternary cathode material is assembled into a battery; The battery undergoes its first charge-discharge cycle, and is then charged to 100% SOC for load adjustment; and After load adjustment, m measurement points are randomly selected on the surface of the positive electrode of the battery. Crushing curve test is performed on each measurement point to obtain m electrode pressure-displacement curves. The number of curves with plateau characteristics in the m pressure-displacement curves is recorded as n, where m≥30 and n≥0. Then the particle breakage index IC=n / m.
10. An electrochemical device, characterized in that, The electrochemical device includes a positive electrode plate, the positive electrode plate includes a positive electrode material, the positive electrode material is a ternary positive electrode material as described in any one of claims 1 to 4 or a ternary positive electrode material prepared by any one of claims 5 to 9.
Citation Information
Patent Citations
High-nickel material coated with Li2TiO3 on surface and doped with Ti on surface layer and preparation method
CN106910874A
Lithium ion battery positive electrode material, preparation method of positive electrode material and application of positive electrode material in lithium ion battery
CN112701264A